Memory as Moral Formation: Intergenerational Storytelling in Psalm 78:1-8 as a Paradigm for Faithful Discipleship - Frans Joases Exaudi Sitio (Global Education Journal, 2026)
Psalm 78:1–8 presents memory not merely as the preservation of Israel's past but as a formative theological practice through which covenant identity, moral character, and faithful discipleship are transmitted across generations. This article investigates how intergenerational storytelling functions as a divinely ordained pedagogical strategy that transforms communal memory into ethical responsibility. Employing a historical-literary and theological exegetical approach, the study analyzes the structure, vocabulary, and theological motifs of Psalm 78:1–8, paying particular attention to the relationship between remembering God's mighty acts, covenant fidelity, and the formation of successive generations. Drawing on theories of collective memory and moral formation, the article argues that biblical remembrance is an active and communal process that shapes identity rather than a passive recollection of historical events. The psalm portrays storytelling as a covenantal practice that cultivates trust in God, obedience to divine instruction, and resilience against the recurring pattern of forgetfulness and rebellion. Furthermore, the study demonstrates that the intergenerational transmission of faith serves as a paradigm for contemporary Christian discipleship, where narrative participation fosters theological imagination and moral formation within families and faith communities. By integrating biblical exegesis with theological reflection, this article contributes to Old Testament scholarship and practical theology by proposing that covenant memory remains an indispensable foundation for sustaining faithful discipleship across generations in an increasingly fragmented and memory-deficient cultural context.